Low-cost high-power-resistant foam glass wave-absorbing material as well as preparation method and application thereof
By using low-cost silicate or glass substrate and wave absorber, foam glass wave absorbing materials are prepared through integrated foam sintering process, solving the problems of high cost and unstable performance of existing high-power wave absorbing materials. , realizes low-cost, efficient wave absorbing performance and environmentally friendly wave absorbing materials.
Patent Information
- Application Number
- CN202411591913.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing high-power absorbing materials have high cost, complex preparation processes, and unstable performance in high-frequency and high-power electromagnetic wave environments, making it difficult to meet the electronics industry's needs for low-cost, high-power resistance and environmental protection.
Use low-cost silicates or other suitable glass as substrates, incorporate low-cost absorbers such as carbon powder and ferrite powder, and prepare porous foam glass absorbers with porous structures through integrated foaming and sintering process. .
It achieves low-cost and efficient wave absorption performance consistent with traditional wave absorption materials, with a temperature resistance of more than 400℃, and is suitable for high-power electromagnetic wave environments above 15KW. The materials are environmentally friendly and easy to process, and meet the requirements of sustainable development.
Smart Images

Figure CN119461862A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing absorbing materials, and in particular relates to a low-cost high-power resistant foam glass absorbing material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic technology, especially the widespread application of wireless communications, radar systems, satellite navigation, and various high-power electronic devices, the electromagnetic environment has become increasingly complex. This has led to increasingly serious electromagnetic compatibility (EMC) problems and electromagnetic interference (EMI) phenomena. The complexity of the electromagnetic environment has led to frequent mutual interference between electronic devices, posing a potential risk of electromagnetic pollution to the physical space where humans live and work, and posing a threat to the security and efficiency of information transmission. In the fields of high-frequency testing and high-power testing, such as radar, satellite communication ground stations, and high-performance computing, the performance requirements for absorbing materials are constantly increasing. Ideal absorbing materials should have the ability to efficiently absorb electromagnetic waves and be able to be exposed to high-power electromagnetic wave radiation for a long time without thermal decomposition, structural damage, or significant performance degradation, thereby ensuring the stable operation of the equipment and accurate transmission of data.
[0003] However, although traditional high-power absorbing materials, such as aramid honeycomb structural materials, silicon carbide / ceramic-based absorbing materials, and foam metal-based absorbing materials, have been widely used in specific fields due to their superior absorbing performance, their high cost and complex preparation process have become key factors limiting their further popularization. Especially in those scenarios where absorbing materials need to be laid over a large area or replaced frequently, cost control becomes an important consideration. In addition, as the concept of environmental protection and sustainable development has become popular around the world, the development of new absorbing materials that are environmentally friendly, recyclable or biodegradable has become a new trend in the development of the industry. Traditional absorbing materials may involve the use of hazardous substances in the production process, and are difficult to handle after being discarded, which does not meet the requirements of green manufacturing and circular economy. Therefore, exploring and promoting the use of non-toxic or low-toxic raw materials, reducing environmental pollution in the production process, and realizing the greening and recyclability of absorbing materials are of great significance to promoting the sustainable development of the electronics industry.
[0004] Based on the above background, the development of a low-cost, high-power absorbing material aims to solve the above problems. The research and development of new materials should fully consider the use of economical, easily available and widely sourced raw materials, and greatly reduce the overall production cost by simplifying the preparation process, optimizing the structural design and other means, while ensuring that the material can still maintain good absorbing performance and long-term stability when subjected to high-power electromagnetic wave radiation, so as to reduce reflection and transmission and effectively suppress electromagnetic interference. Use non-toxic or low-toxic materials to reduce environmental pollution and meet the requirements of sustainable development. By regulating the structure and composition of the material, the adaptability of the material is further improved, and its application range is broadened so that it can adapt to the use requirements under different environmental and frequency conditions, meet the actual needs of multiple fields such as communications, transportation, aerospace, and medical care, and contribute to the promotion of green development of the electronics industry. Summary of the invention
[0005] In view of the above, the purpose of the present invention is to provide a low-cost high-power resistant foam glass absorbing material and a preparation method and application thereof. The material comprises a low-cost silicate or other suitable glass as a substrate, a low-cost absorbing agent such as carbon powder, ferrite powder or other composite absorbing material is added to the substrate, and raw materials such as a foaming agent and a binder are mixed evenly and then formed by an integrated foaming and sintering process. The material can absorb high-power electromagnetic waves, has a temperature resistance of more than 400°C, is flame-retardant, and is easy to process. The absorbing performance is not much different from that of aramid absorbing honeycombs, and the material cost is extremely low. The material is intended to meet the needs of modern radar systems, electromagnetic compatibility (EMC) engineering, and military stealth technology for efficient, economical and durable absorbing materials.
[0006] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:
[0007] In the first aspect, an embodiment of the present invention provides a low-cost, high-power resistant foam glass absorbing material, which is made by uniformly mixing a batch material including glass powder, absorbing filler, foaming agent and binder, and then foaming and sintering them as a whole to form a porous structure including a plurality of closed cells inside and a plurality of open cells on the outer surface.
[0008] Preferably, the mass percentage of the glass powder is 60% to 90%.
[0009] Preferably, the glass powder comprises one or more of sodium calcium silicate, borosilicate, silicon dioxide and aluminum oxide, or is ground into powder using industrial waste glass. The use of inorganic materials such as low melting point and high purity silicate glass powder can ensure heat resistance while avoiding the introduction of harmful substances due to the addition of organic solvents during the preparation process, thus meeting the requirements of low cost and environmental adaptability.
[0010] Preferably, the mass percentage of the wave-absorbing filler is 5% to 35%.
[0011] Preferably, the wave absorbing filler comprises one or more of carbon material and ferrite powder.
[0012] Preferably, the carbon material includes conductive carbon black, conductive carbon fiber, graphite and carbon nanotubes, and the ferrite powder includes manganese zinc ferrite, nickel zinc ferrite and hexagonal ferrite. By selecting a cost-effective absorbing filler, high efficiency absorbing can be achieved at a lower addition amount, thereby reducing costs.
[0013] Preferably, a foaming agent that decomposes under heat is selected to ensure a uniform foaming process, and the resulting pore structure is fine and uniform, and an inorganic binder and an auxiliary agent are selected to enhance the structural strength and durability of the foam glass, while ensuring the overall stability of the material during high temperature treatment.
[0014] In a second aspect, in order to achieve the above-mentioned purpose of the invention, an embodiment of the present invention further provides a method for preparing the above-mentioned low-cost high-power resistant foam glass absorbing material, comprising the following steps:
[0015] Mixing ingredients: Mix the ingredients including glass powder, absorbing filler, foaming agent and binder in proportion using high-speed mixing equipment;
[0016] Molding and sintering: inject the evenly mixed batch into the mold, preheat in an inert atmosphere to remove moisture, and then heat the mold to the foaming temperature to decompose the foaming agent to foam and form a porous structure;
[0017] Annealing and cutting: After sintering, annealing treatment is carried out. After cooling to room temperature, the material is subjected to subsequent processing including cutting, grinding and surface treatment to obtain foam glass absorbing materials that meet the required size.
[0018] Preferably, a high-efficiency mixing device, such as a planetary mixer, is used to fully and evenly mix the glass powder, the absorbing filler, the foaming agent, the binder and the additive to ensure smooth progress of the subsequent processes.
[0019] Preferably, the mixed material is preheated to the activation temperature of the foaming agent, and pre-foamed using a mold or a continuous production line to form a preliminary porous structure. The pre-foamed material is quickly transferred to a molding mold and formed into the desired shape through a compression or injection molding process.
[0020] Preferably, the molding material is sintered in an inert gas protection furnace. During this process, the foaming agent is completely decomposed to produce gas, forming a stable porous foam structure. The sintering temperature and time need to be strictly controlled to ensure that the foam structure is uniform and the porosity is moderate. At the same time, the solid phase reaction of the absorbing filler is completed to improve the absorbing performance of the material.
[0021] Preferably, the preheating temperature is 350-400°C, the foaming temperature is 900-960°C, and the insulation time after foaming is 15-45min; during molding and sintering, the temperature is first increased from room temperature to the preheating temperature at a heating rate of 20°C / min, then increased to 700°C at 5°C / min, and then increased to the foaming temperature at 3°C / min.
[0022] Preferably, after sintering, the material is properly cooled to avoid internal stress caused by rapid cooling, and the sintered material is cut, polished, surface treated and processed as needed. The surface of the shaped material is then treated, impregnated with an interface agent and cured at room temperature for 24 hours, and finally sprayed with an anti-aging, waterproof or conductive coating to enhance the environmental adaptability and specific functions of the material.
[0023] Preferably, the foam glass absorbing material is formed into a flat plate, a pyramid or a triangle, has a thickness of 20 mm to 900 mm, has a high porosity of ≥ 80% and a density of ≤ 0.8 g / cm 3 of low density.
[0024] On the third aspect, in order to achieve the above-mentioned purpose of the invention, the embodiment of the present invention also provides a low-cost, high-power resistant foam glass absorbing material for use in microwave darkrooms, radar stealth technology, aerospace, communication base stations, electronic equipment and laboratories. The above-mentioned low-cost, high-power resistant foam glass absorbing material is used to make solid or hollow lightweight structural parts of various shapes for electromagnetic wave absorption and high power resistance.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) Significant cost savings: Compared with aramid honeycomb, silicon carbide / ceramic-based absorbing materials, and foam metal-based absorbing materials, the raw material cost of foam glass absorbing materials is extremely low and the absorbing effect is not much different from the absorbing performance of current traditional absorbing materials.
[0027] (2) High power tolerance: Compared with the temperature resistance of traditional polyurethane foam absorbing materials used in microwave darkrooms below 100°C and aramid honeycombs below 280°C, foam glass absorbing materials can withstand temperatures above 400°C and can be used in high-power electromagnetic wave environments above 15KW.
[0028] (3) Broadband wave-absorbing properties and light weight: The foam structure of the foam glass absorber is porous, which gives the material efficient wave-absorbing ability over a wide frequency range while reducing the weight of the material.
[0029] (4) Environmental adaptability and ease of processing: During the material design and preparation process, the raw materials are all environmentally friendly inorganic materials. Compared with traditional absorbing materials, the preparation process does not contain polymer resins, organic solvents and other substances that are harmful to the human body. In addition, it also has good processing performance and can be customized in shape and size to meet diverse needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 This is a physical schematic diagram of a low-cost, high-power resistant foam glass absorbing material provided by an embodiment of the present invention;
[0032] Figure 2 It is a schematic flow chart of a method for preparing a low-cost high-power resistant foam glass absorbing material provided by an embodiment of the present invention;
[0033] Figure 3 It is a reflection loss RL curve of a low-cost, high-power resistant foam glass absorbing material with a length, width and height of 180 mm×180 mm×100 mm provided in Example 1 of the present invention;
[0034] Figure 4 The reflection loss RL curve of the low-cost high-power resistant foam glass absorbing material provided in Example 2 of the present invention, wherein the length and width are both 180 mm×180 mm and the heights are 20 mm, 30 mm, 40 mm and 50 mm respectively;
[0035] Figure 5 Schematic diagram of a low-cost high-power resistant foam glass absorbing material having a 3×3 array of pyramid structures cut out in Example 3 of the present invention;
[0036] Figure 6 It is the reflection loss RL curve of the low-cost high-power resistant foam glass absorbing material of Example 3 of the present invention, which has a pyramid base length of 200 mm and a height of 700 mm. DETAILED DESCRIPTION
[0037] To make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.
[0038] The inventive concept of the present invention is: in view of the problems of poor high-power electromagnetic wave resistance and temperature resistance and flame retardancy, high cost, complex preparation process, light weight and environmental adaptability of the absorbing materials in the prior art, the embodiment of the present invention provides a low-cost high-power resistant foam glass absorbing material and preparation method and application, the raw material cost is extremely low and the absorbing effect is not much different from the absorbing performance of the current traditional absorbing materials, the temperature resistance is above 400°C, and it can be used in a high-power electromagnetic wave environment above 15KW. The porous characteristics give the material an efficient absorbing ability in a wide frequency range, while reducing the weight of the material, and the preparation process does not contain polymer resins, organic solvents and other substances harmful to the human body. It is used to meet the requirements of microwave darkrooms, aerospace, radar stealth, communication base stations and electronic equipment for high-power electromagnetic wave absorption, and achieves fire retardancy, low cost and environmental adaptability, has good processing performance, can be customized in shape and size, and has broad application prospects.
[0039] Figure 1 Schematic diagram of a low-cost, high-power foam glass absorbing material provided by an embodiment of the present invention. Figure 1 As shown, the embodiment provides a low-cost high-power resistant foam glass absorbing material, which is made by uniformly mixing a batch material including glass powder, absorbing filler, foaming agent and binder, and then foaming and sintering them as a whole to form a porous structure including a plurality of closed cells inside and a plurality of open cells on the outer surface.
[0040] Figure 2 1 is a schematic flow chart of a method for preparing a low-cost high-power foam glass absorbing material provided by an embodiment of the present invention. Figure 2 As shown, the embodiment also provides a method for preparing a low-cost high-power resistant foam glass absorbing material, comprising the following steps:
[0041] S1, mixing ingredients: mixing the ingredients including glass powder, absorbing filler, foaming agent and binder in proportion using a high-speed mixing device.
[0042] Specifically, firstly, suitable glass powder and absorbing filler are selected and pre-treated including surface modification to enhance the bonding and dispersibility of the two. Then, the crushed glass powder, absorbing filler, foaming agent, foaming promoter, binder, stabilizer and other additives are mixed evenly according to the designed proportion to prepare the batch material of the foam glass, and the batch material is fully mixed using a high-speed mixing device.
[0043] S2, molding and sintering: inject the uniformly mixed batch into the mold, preheat in an inert atmosphere to remove moisture, and then heat the mold to the foaming temperature to decompose the foaming agent by heat to foam and form a porous structure.
[0044] Specifically, the mixed slurry is injected into the mold, and the mold containing the slurry is placed in a preheating furnace and gradually heated from room temperature to about 350-400°C at a heating rate of 20°C / min to remove moisture from the mixture and avoid uneven foaming caused by moisture during sintering. Then the temperature is raised to 700°C at 5°C / min, and then to the foaming temperature at 3°C / min to decompose the foaming agent to generate gas, while ensuring that the foaming process is uniform and a porous structure is formed.
[0045] S3, annealing and cutting: after sintering, annealing treatment is performed, and after cooling to room temperature, the material is subjected to subsequent processing including cutting, grinding and surface treatment to obtain a foam glass absorbing material that meets the required size.
[0046] Specifically, a certain temperature is maintained to stabilize the bubble structure, and the heat preservation time after foaming is 15-45 minutes, followed by annealing to eliminate internal stress, consolidate the porous structure, and ensure the mechanical stability and dimensional stability of the foam glass. After annealing, it is slowly cooled to room temperature, and then the foam glass absorber is removed from the mold. The sintered material is cut, polished, surface treated, and other subsequent processing is performed as needed to meet specific size and appearance requirements.
[0047] Below in conjunction with embodiment 1-3 and Figure 3 , 4 The reflection loss RL curve shown in 6 further verifies the absorbing performance of the low-cost high-power resistant foam glass absorbing material provided by the embodiment of the present invention.
[0048] Example 1
[0049] S101, sodium calcium silicate, borosilicate, silicon dioxide, aluminum trioxide are selected to compound glass powder raw materials, and the glass powder raw materials include 70 parts of silicon dioxide, 15 parts of boron trioxide, 10 parts of sodium oxide, 4 parts of aluminum trioxide, and 1 part of calcium oxide. Among them, the glass powder raw materials account for 70% of the total mass, the conductive carbon black as the wave absorbing filler accounts for 25% of the total mass, the calcium carbonate as the foaming agent accounts for 4% of the total mass, and the glass fiber as the binder accounts for 1% of the total mass. After the above raw materials are accurately weighed according to the proportion, they are evenly mixed using a high-efficiency mixing equipment planetary mixer to ensure that the distribution of each component is consistent. Among them, the ratio of raw materials: ball milling beads: water is 1:1:1.
[0050] S102, injecting the mixed slurry into a mold, placing the mold containing the slurry in a preheating furnace, and gradually heating it to about 350-400° C. at a heating rate of 20° C. / min to remove moisture from the mixture and avoid uneven foaming caused by moisture during sintering.
[0051] S103, heating the mold to 700°C at a heating rate of 5°C / min, and then heating the mold to a predetermined foaming temperature of 900-960°C at a heating rate of 3°C / min, so that the foaming agent is decomposed by heat to generate gas. The heat preservation time after foaming is 30 minutes to ensure a uniform foaming process and form a porous structure.
[0052] S104, performing annealing treatment to eliminate internal stress, consolidate the porous structure, and ensure the mechanical stability and dimensional stability of the foam glass. After annealing, slowly cool to room temperature at a cooling rate of 5°C / min, and then take out the foam glass absorbing material from the mold.
[0053] S105, cutting and grinding the sintered material, the final sample size is 180mm×180mm×100mm. Then the shaped foam glass is impregnated with the interface agent and cured at room temperature for 24 hours to obtain the sample as shown in FIG. Figure 1 shown.
[0054] S106, using the bow method of the vector network analyzer to test its reflection loss RL curve at 1-18GHz is as follows Figure 3 shown.
[0055] Example 2
[0056] S101, waste glass is selected as glass powder raw material, the waste glass is put into a crusher and crushed into powder, and the powder is passed through a 200-mesh sieve to obtain glass powder raw material, wherein the glass powder raw material accounts for 70% of the total mass, the conductive carbon black is used as an absorbing filler, accounting for 25% of the total mass, the calcium carbonate is used as a foaming agent, accounting for 4% of the total mass, and the glass fiber is used as a binder, accounting for 1% of the total mass. After the above raw materials are accurately weighed according to the proportion, they are evenly mixed using a high-efficiency mixing equipment planetary mixer to ensure that the distribution of each component is consistent, wherein the ratio of raw material: ball milling beads: water is 1:1:1.
[0057] S102, same as in Example 1.
[0058] S103, same as in Example 1.
[0059] S104, same as in Example 1.
[0060] S105, cutting and grinding the sintered material, the final sample size is 180 mm × 180 mm in length and width, and 20 mm, 30 mm, 40 mm, and 50 mm in height. Then, the shaped foam glass is impregnated with an interface agent and cured at room temperature for 24 hours.
[0061] S106, using the bow method of the vector network analyzer to test its reflection loss RL curve at 1-18GHz is as follows Figure 4 shown.
[0062] Example 3
[0063] S101, same as in Example 1.
[0064] S102, same as in Example 1.
[0065] S103, same as in Example 1.
[0066] S104, same as in Example 1.
[0067] S105, cutting the sintered foam glass into 3×3 arrayed pyramids, each of which has a base length of 200 mm and a height of 700 mm (the tip of the original pyramid with a height of 900 mm is cut off by 200 mm), such as Figure 5 Then the shaped foam glass is impregnated with the interface agent and cured at room temperature for 24 hours.
[0068] S106, using the coaxial method and bow method of the vector network analyzer to test its reflection loss RL curve at 0.05-2GHz is as follows Figure 6 shown.
[0069] The specific implementation methods described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above is only the most preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-cost high-power foam glass absorbing material, characterized in that: The porous structure is formed by mixing glass powder, wave-absorbing filler, foaming agent and binder uniformly and then foaming and sintering them to form a porous structure including a plurality of closed cells inside and a plurality of open cells on the outer surface.
2. The low-cost high-power resistant foam glass absorbing material according to claim 1, characterized in that: The mass percentage of the glass powder is 60% to 90%.
3. The low-cost high-power resistant foam glass absorbing material according to claim 1, characterized in that: The glass powder is a compound of one or more of soda-lime silicate, borosilicate, silicon dioxide and aluminum oxide, or is ground into powder by industrial waste glass.
4. The low-cost high-power resistant foam glass absorbing material according to claim 1, characterized in that: The mass percentage of the wave absorbing filler is 5% to 35%.
5. The low-cost high-power resistant foam glass absorbing material according to claim 1, characterized in that: The wave absorbing filler includes one or more of carbon material and ferrite powder.
6. The low-cost high-power resistant foam glass absorbing material according to claim 5, characterized in that: The carbon materials include conductive carbon black, conductive carbon fiber, graphite and carbon nanotubes, and the ferrite powder includes manganese zinc ferrite, nickel zinc ferrite and hexagonal ferrite.
7. A method for preparing a low-cost high-power resistant foam glass absorbing material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing ingredients: Mix the ingredients including glass powder, wave-absorbing filler, foaming agent and binder evenly according to the proportion using high-speed mixing equipment; Molding and sintering: inject the mixed batch into the mold, preheat in an inert atmosphere to remove moisture, and then heat the mold to the foaming temperature to decompose the foaming agent to form a porous structure; Annealing and cutting: After sintering, annealing treatment is carried out. After cooling to room temperature, the material is subjected to subsequent processing including cutting, grinding and surface treatment to obtain foam glass absorbing materials that meet the required size.
8. The method for preparing a low-cost high-power resistant foam glass absorbing material according to claim 7, characterized in that: The preheating temperature is 350-400°C, the foaming temperature is 900-960°C, and the insulation time after foaming is 15-45min; during molding and sintering, the temperature is first increased from room temperature to the preheating temperature at a heating rate of 20°C / min, then increased to 700°C at 5°C / min, and then increased to the foaming temperature at 3°C / min.
9. The method for preparing a low-cost high-power resistant foam glass absorbing material according to claim 7, characterized in that: The foam glass absorber has a flat, pyramidal or triangular shape with a thickness of 20 mm to 900 mm, a high porosity of ≥ 80% and a density of ≤ 0.8 g / cm 3 of low density.
10. Application of low-cost high-power foam glass absorbing material in microwave darkroom, radar stealth technology, aerospace, communication base station, electronic equipment and laboratory, characterized in that: The low-cost high-power-resistant foam glass absorbing material described in any one of claims 1 to 6 is used to manufacture solid or hollow lightweight structural parts of various shapes for electromagnetic wave absorption and high-power resistance.